2015
DOI: 10.1007/s12253-015-9992-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of mannose binding lectin on fever episodes in pediatric oncology patients

Abstract: Despite significant changes in pediatric oncological therapy, mortality is still high, mainly due to infections. Complement system as an ancient immune defense against microorganisms plays a significant role in surmounting infections, therefore, deficiency of its components may have particular importance in malignancies. The present paper assesses the effect of promoter (X/Y) and exon 1 (A/0) polymorphisms of the MBL2 gene altering mannose binding lectin (MBL) serum level in pediatric oncological patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
2
1
1
Order By: Relevance
“…However, the definition of bacterial BSI and septic shock is not identical, hampering the comparisons of these two studies. Previous studies investigating MBL deficiency in children with cancer have reported contradictory results [8][9][10][11]14,15,39], whilst we could not show any association between MBL sequence variants and FN during the treatment for childhood ALL. Consequently, the present study strengthens the evidence that MBL does not play a role during episodes of FN and associated MDI.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, the definition of bacterial BSI and septic shock is not identical, hampering the comparisons of these two studies. Previous studies investigating MBL deficiency in children with cancer have reported contradictory results [8][9][10][11]14,15,39], whilst we could not show any association between MBL sequence variants and FN during the treatment for childhood ALL. Consequently, the present study strengthens the evidence that MBL does not play a role during episodes of FN and associated MDI.…”
Section: Discussioncontrasting
confidence: 99%
“…Sequence variants in the TLR4 have been associated with an increased risk of sepsis, Gram-negative BSI, as well as the development of chemotherapy-induced neutropenia [11][12][13]. Data regarding sequence variants in the MBL and risk of FN in children during chemotherapy are inconclusive, with studies indicating an increased risk of bacterial infection, whilst some studies do not suggest any correlation to FN or any other MDI [9][10][11]14,15]. The IL1RN*2 allele has been associated with an increase in the susceptibility to sepsis and clinically severe sepsis in adults, but also to an increased risk of septic shock in children with ALL [7,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Exploratory studies on their health benefits have been initiated, because lectins have important physiological roles, including insecticidal action [3,6], antibacterial activity [7], and antifungal effects [8], antihuman immunodeficiency virus [9], antitumor activity [10,11,12], and analgesic activity [13]. Plants are the main source of lectins that are found in different parts of plants such as seeds, leaves, bark, roots, tubers, and fruits [14].…”
Section: Introductionmentioning
confidence: 99%
“…Манноза является неза-менимым углеводным компонентом имму-ноглобулинов и других биологически активных веществ, обладает пребиотическим действием [1]. Исследования показали, что этот углевод выполняет важную роль в живом организме [2,3], и может быть использован для профилактики и лечения урологических инфекций [4], диабета [5] и углевод-дефицитных гликопротеиновых синдромов I и II типов [6].…”
Section: биотехнология и бионанотехнологияunclassified